Integrating family farmers’ perceptions with meteorological records and national climate change projections to enhance site-specific adaptation knowledge - Enriquez, Andrea Soledad; Fernandez, Manuela Teresa; Aramayo, Maria Valeria Del Lu; De Pascuale Bovi, Juan Alberto; Ocariz, María Paula; Tittonell, Pablo Adrian (Springer, 2023)
Adaptation strategies to climate change (CC) that do not consider local perspectives tend to fail at specifc sites. Searching for complementary actions, we aimed to assess how farmers’ perceptions about climatic hazards match past and future climate data. An original common coding was developed to combine qualitative and quantitative data using climate trend indicators. In our case study, we compared climate perceptions of family farmers from seven localities of northern Patagonia, Argentina, collected from seven participatory risk assessment workshops, with meteorological records from six local weather stations (1999–2020) and national projected CC scenarios (simulations to 2039). In the context of a semiarid region, people’s greatest concern was found to be focused on the scarcity of water resources. Despite this focus, results showed that temperature (T) had greater predictability from farmers than precipitation (P): perceptions were better associated with past and future T variable trends (T mean, T min, and T max), than with P ones (average rainfall and number of days with rainfall events>10 mm). We discussed social and technical causes of matches or mismatches among the views. The information resulting from the comparison of perceived climatic hazards and climate data can be used to improve climate communication with farmers, to collectively assess, design, and prioritize site-specifc adaptation measures and future actions. The detailed description of our methodology would allow others to take advantage of local and technical knowledge to overcome climate change challenges.